Factors Affecting the Decline in Childbearing in Iran: A Systematic Review - Baki-Hashemi, Sara; Kariman, Nourossadat; Ghanbari, Shahla; Pourhoseingholi, Mohammad-Amin; Moradi, Maryam (Advances in Nursing & Midwifery, 2018)
Abstract Introduction: The decline in fertility and childbearing tendency in Iran is due to various demographic, economic, social, and cultural variables. The present research was conducted to review studies carried out on factors affecting the decline in childbearing. Methods: This systematic review searched for articles published from 2011 to 2017 in all the available Iranian and foreign databases, including SID, Magiran, Irandoc, Medlib, Pubmed, Google Scholar, Science Direct, and Proquest using the following keywords, “childbearing”, “fertility”, “fertility decline” and “population decline”. The search ultimately led to the inclusion of 53 studies. Results: The main factors affecting the decline in childbearing discussed in the 53 reviewed articles were divided to three general categories: 1. Personal and family factors, including aging, older age at marriage, current number of children, the duration of marriage, the mean birth spacing, gender preferences, hopefulness, marital satisfaction, and quality of life, 2. Socioeconomic factors, including social support, education, occupation and social participation, especially of females, place of residence and the effect of social networks, 3. Cultural factors, including modernity, urbanization and industrialization, attitude change towards the value of children, changes in family values and religion. Conclusions: To intervene in the decline in childbearing and to increase the success rate of the designed plans and strategies, policy-makers and planners should provide strategies to deal with all the three noted groups of factors affecting childbearing.